Penggunaan Teknik Talking Chips pada Model Kooperatif Hasil Belajar dalam Pembelajaran Tata Nama Senyawa dan Persamaan Reaksi Kimia di SMAN 2 Pariaman - Bayharti, Bayharti; Bahrizal, Bahrizal; Fitriani, Rahmi (Jambura Journal of Educational Chemistry, 2017)
The goal of this study is to know the effect of using techniques talking chips on the cooperative learning in study of nomenclature of compounds and the chemical reaction at SMAN 2 Pariaman. The model used is a cooperative learning with talking chips technique that can improve students' learning activity. This research is a quasi-experimental research which design of Randomized Control Group Posttest Only Design. The population of this study were all students of class X SMAN 2 Pariaman. The sampling technique used was cluster sampling X.1 class is experimental and X.2 class is the control class. The data collection was done by administering tests at the end of the study. This research found that the average value of student score at experimental class is 76.33 and those of control class is 69.4. Both of these data are found normal and homogen. Data analysis used was t-test on a real level of 0.05 that obtained tcount = 2.605 and ttabel1.67. This means tcount> ttabel, and the research hypothesis is accepted. It can be concluded that there is a significant increase from the results of studying chemistry by using the technique of talking chips on the cooperative model in study of nomenclature of compounds and chemical equations.